Community participation in protected area management of Taman Negara National Park, Pahang, Malaysia / Mohd Salleh Daim - Daim, Mohd Salleh (2016)
Within the theoretical concepts community participation has been used or explored in many fields as an approach for conflict resolution. In the field of natural resource management, recognising the rights and responsibility of local community neighbouring to natural areas has become vital to complement the traditional management approach especially in protected area management. One of the prevalent issues in the field of protected area management would be the relationship between the protected area and its neighbours. This bittersweet relationship is loaded with protected area management theories and principles adopted by most management agencies mixed with the moral, values and norms of local community who often reside within or in close proximity to these protected areas. This thesis explores the dynamic of participatory approach in protected area management. This thesis deals with the long overdue issue of local community versus protected area, by exploring one example pertinent to Malaysia which is the Taman Negara National Park and its neighbours. Briefly, it intends to examine the issues, concerns and opportunities of participatory approach in protected area management in Peninsular Malaysia. Specifically, it examines the benefits of community participation and its relationship with community acceptance on the types or levels of participation suitable in protected area management. One primary case has been selected for this study which is Taman Negara National Park, Pahang, Malaysia. A total of 290 respondents from ten villages consist of seven Malay villages and three Orang Asal villages neighbouring to Taman Negara National Park, Pahang were selected and interviewed face-to-face using a questionnaire. The data were analysed using discriptive statistics, factor analysis, and Partial Least Square SEM (PLS-SEM) technique. Drawing from the empirical evidence gathered from this study, the findings are: 1) community participation in TNNP management is very minimal and at a lower level of participation, 2) economic, social, legal and institutional, and attitudinal benefits tested as benefits of community participation do have significant influence to the villagers' acceptance on the types or levels of participation suitable for TNNP management. Legal and institutional benefit is the benefit that influences villagers' view the most on community participation in protected area management. Overall, it can be concluded that as the benefits of community participation among local community improve, their acceptance to participate in the highest level of participation also increase. This information may be of use in addressing the policyrelated issues concerning the roles of neighbours and the management of protected areas in sustainable development.